PHYSICAL TRAINING OF AN ATHLETE - Gapparov Khafiz Zakhidovich; Hikmatilla Rakhmanberdievich Akhmedov (Scholar Express Journal, 2022)
The article considers the main factors of the athlete's physical training. It shows the relationship of technical and tactical training, psychological and moral-volitional training. The issues of general and special physical training are also considered.
Keywords: Physical training; technical and tactical training; psychological training